The Theology of Islamic Education from Salafi and Liberal Perspectives. Issue 4 (8th August 2018) - Saada, Najwan
Abstract: This article examines the tenets of today's two contemporary traditions in Islam, neo-traditional Salafism and liberal or progressive Islam and analyzes how they cultivate a typology of Islamic religious education. The typology under study clarifies the meaning of tarbi yya and ta`dib in Islamic educational philosophy and demonstrates the place of these goals within a continuum of critical versus noncritical talim (teaching) in Islamic religious education. The purpose of this typology is to provide both scholars and practitioners a theoretical framework for thought and reflection about their pedagogic methods and scholarly work.